Pengaruh waktu dan konsentrasi NaOH pada proses delignifikasi wheat bran - Devi Sepmita Wulansari; Supranto Supranto (Jurnal Rekayasa Proses, 2016)
There are approximately 14.5% of whole wheat which belongs to bran and contains cellulose (33.7-40%), hemicellulose (21-26%), lignin (11–22.9%) and the other components. Cellulose is polysaccharide which is composed of 2000-3000 unit of glucose. Cellulose purification from the wheat bran can be done by the hydrolysis, followed by the processes of delignification and bleaching. The experiments were perfomed first by hydrolizing 20 grams of wheat bran using 250 mL of 2.5 N HCl solution for 2 hours at temperature of 80oC. The next process was delignification using 400 mL of NaOH solution and was conducted by varying the time in 1 hour, 1,5 hours, 2 hours, and 2.5 hours and the concentration of NaOH solution in 0.5 N; 1 N; 1.5 N; 2 N. For the last process, bleaching was performed by using 300 mL of H2O2 10% solution in temperature of 80 oC for 1 hour. The sample was then dried in order to remove water content by getting the sample in the oven for 1 hour at temperature of 40 oC. The goals of the experiments were to find the correlation between the variation of time and NaOH concentration to the cellulose quality in terms of the color and the structure of cellulose sample and and to the quantitative measure which was the yield of the sample. The best product was obtained at the optimum operation of 2.5 hours delignification and 1.55 N of NaOH concentration.